CXC and CC Chemokines as Angiogenic Modulators in Nonhaematological Tumors. (29th May 2014) - Santoni, Matteo; Bracarda, Sergio; Nabissi, Massimo; Massari, Francesco; Conti, Alessandro; Bria, Emilio; Tortora, Giampaolo; Santoni, Giorgio; Cascinu, Stefano
Abstract : Chemokines are a superfamily of structurally homologous heparin-binding proteins that includes potent inducers and inhibitors of angiogenesis. The imbalance between angiogenic and angiostatic chemokine activities can lead to abnormalities, such as chronic inflammation, dysplastic transformation, and even tumor development and spreading. In this review, we summarize the current literature regarding the role of chemokines as modulators of tumor angiogenesis and their potential role as therapeutic targets in patients with nonhaematological tumors.